Pengaruh Digitalisasi Marketing, Brand Image, Dan Diferensiasi Produk Terhadap Keputusan Pembelian Produk Eiger - Rizal Rahmatulloh; Pardiman Pardiman; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research seeks to examine how digital marketing, brand perception, and product distinctiveness impact the choices individuals make when purchasing Eiger products. The research employs a quantitative approach, and the sample selection utilizes purposive sampling guided by the Malhotra formula. This results in a total sample size of 95 partisipants. The data analysis methodology employed is quantitative, specifically employing multiple linear regression analysis. The data is subjected to simultaneous hypothesis testing (F-test) as well as partial hypothesis testing (t-test). The findings of the study indicate that both digital marketing and brand image, along with product differentiation, collectively and individually exert a positive and noteworthy influence on the purchasing decisions concerning Eiger products. Keywords: Marketing Digitalization, Brand Image, and Product Differentiation and Eiger Product Purchasing Decisions.